Letter of Sir Munro to the President of the General Assembly on the Soviet Union Attitude Towards Congo and Cuba that Contrasts with Attitude to Hungary - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Leslie Munro Sir Leslie Munro expresses his bewilderment regarding the Soviet attitude towards foreign intervention in Congo and Cuba. The Soviet Foreign Minister demanded that Belgians to leave Congo immediately. In the case of Cuba, the Soviet Union set itself as a champion against any "economic aggression" and on the side of any small county struggling for independence, against colonialism and foreign exploitation. The letter points to a shameless inconsistency with Soviet actions in Hungary where the Soviet army so brutally repressed the struggle for independence